The Effect of Discounts and Price on Purchase Decisions of GoFood Services among Generation Z Students at Universitas Negeri Jakarta with Perceived Value as a Mediating Variable - Fikri Pirmansyah; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
Pricing strategies are vital in guiding consumer decisions on digital platforms, especially in online food delivery apps. This research examines how discounts and pricing affect purchase choices, highlighting perceived value as a key mediator. The study targets Generation Z students at Universitas Negeri Jakarta, a group known for high digital literacy and frequent use of GoFood. Using a quantitative method, data were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) from responses gathered via structured questionnaires. Results show that both discounts and price significantly impact perceived value, which in turn increases the probability of purchase. However, discounts do not directly influence purchase decisions, implying that price discounts alone are not enough unless they add perceived value. Conversely, price directly affects purchasing, indicating that fairness and affordability are crucial for Generation Z. Mediation analysis confirms perceived value as an essential link between pricing strategies and purchase decisions. Focusing on actual buying behavior rather than intent provides a clearer insight into value-based decision-making in online food delivery. The study suggests platforms targeting Generation Z should focus on pricing strategies that improve perceived value rather than relying only on discounts.